The Bacterial Community in Questing Ticks From Khao Yai National Park in Thailand - Takhampunya, Ratree; Sakolvaree, Jira; Chanarat, Nitima; Youngdech, Nittayaphon; Phonjatturas, Kritsawan; Promsathaporn, Sommai; Tippayachai, Bousaraporn; Tachavarong, Wirunya; Srinoppawan, Kanchit; Poole-Smith, Betty K.; McCardle, P. Wesley; Chaorattanakawee, Suwanna (Frontiers in Veterinary Science, 2021)
Ticks are known vectors for a variety of pathogens including bacteria, viruses, fungi, and parasites. In this study, bacterial communities were investigated in active life stages of three tick genera, (Haemaphysalis, Dermacentor, and Amblyomma) collected from Khao Yai National Park in Thailand. Four hundred and forty-four questing ticks were selected for pathogen detection individually using real-time PCR assays and 58 of these were subjected to further metagenomics analysis. A total of 62 ticks were found to be infected with pathogenic bacteria, for a 14.3% prevalence rate, with Ampblyomma spp. exhibiting the highest infection rate (20.5%), followed by Haemaphysalis spp. (14.5%), and Dermacentor spp. (8.6%). Rickettsia spp. were the most prevalent bacteria (7.9%) found, followed by Ehrlichia spp. (3.2%), and Anaplasma spp. and Borrelia spp. each with a similar prevalence of 1.6%. Co-infection between pathogenic bacteria was only detected in three Haemaphysalis females and all co-infections were between Rickettsia spp. and Anaplasmataceae (Ehrlichia spp. or Anaplasma spp.), accounting for 4.6% of infected ticks or 0.7% of all examined questing ticks. The prevalence of the Coxiella endosymbiont was also investigated. Of ticks tested, 65.8% were positive for the Coxiella endosymbiont, with the highest infection rate in nymphs (86.7%), followed by females (83.4%). Among tick genera, Haemaphysalis exhibited the highest prevalence of infection with the Coxiella endosymbiont. Ticks harboring the Coxiella endosymbiont were more likely to be infected with Ehrlichia spp. or Rickettsia spp. than those without, with statistical significance for Ehrlichia spp. infection in particular (p-values = 0.003 and 0.917 for Ehrlichia spp. and Rickettsia spp., respectively). Profiling the bacterial community in ticks using metagenomics revealed distinct, predominant bacterial taxa in tick genera. Alpha and beta diversities analyses showed that the bacterial community diversity and composition in Haemaphysalis spp. was significantly different from Amblyomma spp. However, when examining bacterial diversity among tick life stages (larva, nymph, adult) in Haemaphysalis spp., no significant difference among life stages was detected. These results provide valuable information on the bacterial community composition and co-infection rates in questing ticks in Thailand, with implications for animal and human health.